CONGRATULATING UTTERANCES OF THE ENGAGEMENT OF THE PRINCE OF ENGLAND (A SOCIO-PRAGMATICS APPROACH) - Aryani, May Ana Putri (2011)
This research is aimed at describing of the intention of congratulating utterances and the types of address form used by the addressor to the addresseein the congratulating utterances of the Prince of England. In achieving the objectives, the researcher uses descriptive qualitative as the type of the research. The data source of this research is facebook Prince of Whales. In collecting the data, the researcher uses documentation method, and the steps are Searching for congratulating utterance of the engagement of the Prince of England from the internet, Gathering the data of congratulating utterances, Classifying speaker's intention and the types of address form of congratulating utterances. The result of the data shows first, the intention of congratulating utterances of the engagement of the prince of England are congratulation followed by wish (34, 3%), congratulation followed by pray (14, 3), congratulation followed by wish and pray (5, 7%), congratulation followed by compliment (17, 1%), congratulation followed by compliment and wish (2, 9%), congratulation followed by hope (5, 7%), congratulation followed by happiness expression (2, 9%), congratulation preceded by wish (8, 5%), congratulation preceded by insult (2, 9%), and congratulation preceded by happiness expression (5, 7%). Second, the address form that used by addressor to the addressee (Prince William) are addressing using aristocratic title (37, 1%), addressing using name (22, 6), addressing using title plus name (28, 6%), addressing using nickname (8, 6%), and does not use address form (2, 9%).